2020
DOI: 10.1093/crocol/otaa037
|View full text |Cite
|
Sign up to set email alerts
|

Functional Molecular Network Analysis Enables Prediction of Response to Vedolizumab Therapy in Anti-TNF Refractory IBD Patients

Abstract: Background We applied for the first time 2 label-free technologies, physiological intermolecular modulation spectroscopy (PIMS) and nematic protein organization technic (NPOT) in anti-tumor necrosis factor (TNF) refractory inflammatory bowel disease (IBD) patients to identify clinical responders to vedolizumab therapy and elucidate their underlying functional molecular network. Methods PIMS analysis was performed in periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Molecular studies have shown some evidence on predictors of response to vedolizumab, but these have been carried out in small numbers. 7 Although there have been studies into predictors of primary response to induction therapy, there have been limited investigations into predictors of sustained response during maintenance therapy. Previous studies of sustained remission have mainly focused on tumor necrosis factor inhibitor (TNFi) therapies or been conducted in pediatric cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular studies have shown some evidence on predictors of response to vedolizumab, but these have been carried out in small numbers. 7 Although there have been studies into predictors of primary response to induction therapy, there have been limited investigations into predictors of sustained response during maintenance therapy. Previous studies of sustained remission have mainly focused on tumor necrosis factor inhibitor (TNFi) therapies or been conducted in pediatric cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…In our cohort, patients with UC with previous exposure to anti-TNF or VDZ, but not both, frequently achieved clinical remission and response rates compared with those with previous exposure to both anti-TNF and VDZ. Previous studies have reported that patients with UC who were nonresponders to VDZ following failure to respond to anti-TNF antibody had higher levels of serum IL-6 30 and mucosal infiltration of eosinophils 31 than those who were responders to VDZ following failure to respond to anti-TNF antibody. Previous studies have indicated that eosinophilia led to the release of Th2-related cytokines, including IL-5 and IL-13, which are suggested to be associated with disease severity and complicated UC course.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that elevated mucosal OSM transcripts were associated with increased inflammatory activity and failure of anti-TNF therapy. 25,26 In a recent study in patients treated with a monoclonal antibody against MaDCAM-1, a significant association was demonstrated between OSM gene expression in inflamed mucosal biopsies and treatment efficacy, although a predictive value of pretreatment expression of OSM was not reported. 18 Despite the aforementioned differences, our current work and those previous studies show the feasibility of pretreatment profiling of patients subjected to biological therapies and the potential for discovering mucosal signatures with predictive value for subsequent response to treatment.…”
Section: Discussionmentioning
confidence: 99%